RADEC Model in IPAS Learning Outcomes of Fifth Grade Students: Model RADEC dalam Hasil Belajar IPAS Siswa Kelas V SD - Layla Najma Nurfand; Irwan Baadilla (Academia Open, 2025)
General Background: The RADEC (Read, Answer, Discuss, Explain, and Create) learning model has gained attention as an innovative approach aligned with 21st-century skills. Specific Background: In SDN Susukan 04 Pagi, low IPAS learning outcomes—particularly on the topic of light and the human eye—highlight the need for more effective instructional strategies. Knowledge Gap: Previous studies on RADEC have mostly addressed narrative or procedural topics and rarely focused on higher-order thinking in abstract scientific content. Aims: This study aims to examine the effect of the RADEC learning model on fifth-grade students’ cognitive outcomes in IPAS. Results: Using a quasi-experimental design with 62 students, findings show that the experimental group, taught using RADEC, scored significantly higher than the control group, with a mean N-Gain of 0.53 (moderate category), compared to 0.24 (low category) in the control group. Novelty: This study applies RADEC to a scientific topic requiring deep conceptual understanding, targeting higher-order cognitive levels (C4–C6). Implications: The results confirm that RADEC improves IPAS learning outcomes and supports its relevance for elementary education, particularly within the framework of the Merdeka Curriculum and differentiated learning.Highlight : RADEC model improves IPAS learning outcomes, especially in higher-order thinking skills (C4–C6). The study shows increased student mastery using RADEC compared to conventional models. RADEC supports active, creative, and student-centered learning aligned with the Merdeka Curriculum. Keywords : RADEC, IPAS, Learning Outcomes, Fifth Grade Students, HOTS